The position of the United States of America on the 1932 coup in Siam - Abdullah, Lect. Dr. Kawthar Abdul Hassan (Thi Qar Arts Journal, 2023)
This research studies the main role that Siam played in the development of the American foreign military policy in Indochina, as the stability of Thailand is one of the main considerations that the American administration takes into account. Therefore, we find that the United States dealt with caution with the 1932 coup against the monarchy in Siam.